The In silico and In vitro Anti-inflammatory and Antibacterial Activities of Flavonoids from Artemisia vulgaris in Vietnam - Trinh, Pham Thi N.; An, Tran Nguyen Minh; Danh, Tong Thanh; Nguyen Thi, Hong Anh; Nguyen, Van-Kieu; Duong, Thuc-Huy; Dung, Le Tien (Current Organic Chemistry, 2023)
Artemisia vulgaris is used to treat rheumatism, scabies, and trauma-related pain in traditional Vietnamese medicine. However, there is a lack of in vitro and in silico studies on the antibacterial and anti-inflammatory effects of Artemisia vulgaris in Vietnam. This research was designed to evaluate the bioactivities of extracts and isolated flavonoids from this plant. The results indicated that crude extract (AVE) and sub-fractions (hexane - AVH; ethyl acetate - AVEA; and methanol - AVM) showed a strong suppression of nitric oxide creation and proinflammatory TNF-α secretion in LPS-activated RAW 264.7 macrophages. Moreover, AVE, AVEA, and AVH demonstrated moderate antibacterial activity against Methicillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa strains with MICs of 2 mg/mL. Among five isolated flavonoids (1-5), apigenin (1) attenuated LPS-induced inflammation in RAW 264.7 macrophages by downregulating TNF-a and NO production, while apigenin (1) and luteolin (2) were the effective inhibitors of MRSA and P. aeruginosa strains. These results are in accordance with in-silico molecular docking investigations. Among docking poses of compounds (1-5), pose 483, the best docking pose among 500 docking conformations of compound apigenin (1), has been docked to the 4WCU:PDB enzyme with the values of the binding affinity and inhibition constant of -7.27 Kcal.mol-1 and 4.73 μM, respectively and proved to be the best anti-inflammatory compound that linked well to this enzyme and was responsible for explaining anti-inflammatory activity. In silico docking to explain why luteolin (2) inhibits bacteria via a general enzyme inhibition mechanism, glucosamine-6-phosphate synthase: 2VF5. Luteolin (2) or pose 148 anchored well to 2VF5 with binding affinity and inhibition constants of -6.90 Kcal.mol-1 and 8.80 μM, respectively. The study demonstrated that apigenin, or pose 483, was an excellent anti-inflammatory compound with meta-hydroxy in ring B, while luteolin, or pose 148, with orto-hydroxy in ring B, exhibited good anti-bacterial activity.
Keywords: flavonoid